Review of Maqasid Syariah in Using Shopee Paylater Islamic Worldview Analysis Study - Hasan Sulton (Penerbit Hellow Pustaka, 2026)
This article examines the use of Shopee PayLater as a payment method on the Shopee e-commerce platform from the perspective of Maqasid Sharia (the objectives of Islamic law). While Shopee PayLater offers convenience and flexibility in online shopping by providing instant credit—allowing customers to receive goods first and pay later or via installments—it entails significant risks, primarily the potential for uncontrolled consumerist behavior that can lead to debt accumulation. Furthermore, the presence of *riba* (usury) elements in the installment system and the imposition of late fees mean that this feature does not fully align with Islamic economic principles. This study employs a literature review methodology. The findings indicate that although Shopee PayLater offers transactional convenience, its use requires caution and careful consideration, particularly within the context of Sharia law. It is crucial for consumers to understand the associated risks and ensure their actions align with Islamic teachings, given the potential harms (*mudharat*) inherent in these transactions—specifically regarding the preservation of wealth (*hifz al-mal*) and the avoidance of practices that contravene Sharia.